2015
DOI: 10.1242/dev.113811
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K reduces hypermineralisation in zebrafish models of PXE and GACI

Abstract: The mineralisation disorder pseudoxanthoma elasticum (PXE) is associated with mutations in the transporter protein ABCC6. Patients with PXE suffer from calcified lesions in the skin, eyes and vasculature, and PXE is related to a more severe vascular calcification syndrome called generalised arterial calcification of infancy (GACI). Mutations in ABCC6 are linked to reduced levels of circulating vitamin K. Here, we describe a mutation in the zebrafish (Danio rerio) orthologue abcc6a, which results in extensive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 45 publications
11
59
0
Order By: Relevance
“…Such analysis provided further insights into the mineralogenic effects related to bone density or ray thickness and is, therefore, a complement to other techniques that infer on the organization of the regenerated mineral, such as birefringence analysis1358, for the identification of pro- or anti-mineralogenic agents with effects not as evident as those of RA, for example. Our data confirmed the role of WARF in negatively regulating mineral density in zebrafish lepidotrichia, in a way contrasting to that described for the abcc6a mutant57. This can be simply explained by the fact that those are two distinct mineralizing systems.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Such analysis provided further insights into the mineralogenic effects related to bone density or ray thickness and is, therefore, a complement to other techniques that infer on the organization of the regenerated mineral, such as birefringence analysis1358, for the identification of pro- or anti-mineralogenic agents with effects not as evident as those of RA, for example. Our data confirmed the role of WARF in negatively regulating mineral density in zebrafish lepidotrichia, in a way contrasting to that described for the abcc6a mutant57. This can be simply explained by the fact that those are two distinct mineralizing systems.…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, in vitro studies reported an inhibition of osteoblast differentiation upon WARF exposure54, while VK media supplementation promoted osteoblast-to-osteocyte transition and decreased osteoclast differentiation5556. Exposure of zebrafish to WARF was found to induce pathological calcification of soft tissues and altered skeletal development during larval stages27, and to promote axial skeleton mineralization in an abcc6a mutant, while VK inhibited bone matrix mineralization57.…”
Section: Resultsmentioning
confidence: 99%
“…1C-E), appearing like a subtle craniosynostosis. However, this ectopic mineralization does not seem to occur in intercalvarial regions, but primarily in the adjacent dermis, as described for diseases such as pseudoxanthoma elasticum (PXE) (Apschner et al, 2014;Mackay et al, 2015;Walker et al, 1989). Indeed, both dermal fibroblasts and basal keratinocytes express col1a2 (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…On the basis of animal model experiments, it has also been hypothesized that low vitamin K export from the liver would decrease the gamma-carboxylation of anti-mineralization proteins [76, 77]. Furthermore, MGP is not carboxylated in the elastic fibers of PXE patients [78], and PXE-like calcification of elastic fibers is observed in patients with mutation in the GGCX gene [78].…”
Section: Etiologymentioning
confidence: 99%
“…Most of the detailed experimental data on the pathophysiology of PXE comes from Abcc6 -deficient models in the zebrafish [77, 96, 97] and in the mouse [98102]. The zebrafish model is a useful tool for testing potential therapies, such as premature termination codon read-through [103].…”
Section: Etiologymentioning
confidence: 99%